Fetomaternal Outcome of Pregnant Women at Term Undergoing Cesarean Section - Bharati, Sonu; Dangal, Ganesh; Tiwari, Kenusha Devi; Maharjan, Sunita; Bhandari, Srijana; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin (Journal of Nepal Health Research Council, 2024)
Background: Cesarean section is one of the most common procedures performed in obstetric practice today and is a lifesaving surgery for mother and fetus. Cesarean sections are classified traditionally, as elective cesarean section or emergency cesarean. The purpose of this study is to compare the maternal and neonatal outcomes in elective and emergency cesarean section so that measures can be taken to reduce maternal and neonatal morbidity and mortality. Methods: A descriptive study including 400 pregnant women who underwent caesarean section were included in this study. Patients were subjected to elective or emergency cesarean section as per the indication and protocol of institute. were included in the study. Results: During the study period there were total 1080 deliveries. The average age of the women was 29.21±4.07 years. Of the 400 cesarean section cases, only 2.8% had wound infection, 3.8% had fever, 4.8% urinary tract infection (UTI) whereas no women had observed with post-partum hemorrhages (PPH) and maternal death. Regarding fetal outcome, neonatal intensive care unit (NICU) admission was observed in 16%, birth asphyxia was 2.3% poor Apgar score 2.5% and neonatal death was not observed. Rate of fever, UTI, wound infection, need of resuscitation and poor Apgar score was significantly high in emergency section than elective caesarean section whereas NICU admission was not statistically significant. The most common indication of emergency cesarean section were fetal dress and for previous LSCS. Conclusions: Emergency cesarean was associated with increased maternal and perinatal complications than in elective cesarean section. Keywords: Caesarean section; elective caesarean section; emergency caesarean section; neonatal morbidity and mortality.